THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION - Prabowo, Thoni Setyo; Noermijati, Noermijati; Irawanto, Dodi Wirawan (Universitas Brawijaya, Indonesia, 2018)
This research aims to examine and to analyze the influence of transformational leadershipand work motivation on employee performance Hotel Kartika Graha Malang in Indonesia either through or without through job satisfaction.This study used a sample of 78 employees of Hotel Kartika Graha Malang in Indonesia. This research applies quantitative analysis by using explanatory study. The data is analyzed by using PLS for significant test and Sobel test for mediating test. The result shows that transformational leadership has no significant influence on employee performance but has significant influence toward job satisfaction. Nevertheless, work motivation has a significant influence on both employee performance and job satisfaction. Moreover, job satisfaction has a significant influence on employee performance. Job satisfaction is also fully mediated the influence of transformational leadership toward employee performance and partially mediated the influence of work motivation toward employee performance. The indicator that causes the non-significant influence of the transformational leadership toward employee performance is an individualized consideration, which is not running optimally in Hotel Kartika Graha.